MITOCHONDRIAL ACTIVITY INHIBITORS OF CANCER-INITIATING CELLS AND USE THEREOF - CLEMENT, VIRGINIE; RADOVANOVIC, IVAN (2012)
The present invention relates to the compounds useful in the prevention and/or treatment of tumors. More specifically the present invention relates to inhibitors of the activity of the electron transport chains and/or the mitochondrial TCA cycle in glioma-initiating cells (GICs) for use in a method for preventing and/or treating tumors presenting glioma-initiating cells (GICs) in a subject who has undergone a prior removal of a tumor glioma bulk. The present invention further provides a pharmaceutical composition containing the inhibitors of the invention and a screening method for identifying the inhibitors of the invention.